Peningkatan Kualitas Produk Fueltank Pada Proses Welding Dengan Metode Six Sigma Pada Industri Manfaktur - Indraswari, Rena Ferlina; Puteri, Renty Anugerah Mahaji (JURNAL TEKNIK INDUSTRI, 2022)
In Indonesia there are many manufacturing companies, one of which is specialized in manufacturing the automotive industry. An automotive industry manufacturing company located in Karawang, West Java, manufactures products including body parts, fuel tanks, dies, Jigs and after sales services. The problem experienced by this company is the high level of product defects produced in the welding process which causes problems. This is the basis for carrying out research in providing quality improvement proposals to reduce the level of defects in products. This study discusses improvements made to the welding production process for fuel tank products. The repair method used is six sigma through the DMAIC stage. The results of the study show that the DPMO value for the welding process of fuel tank products from October 2021 to March 2022 is 69004.855 and the sigma level is 2.98. After the correction was made from December 2021 to February 2022, the DPMO value became 39450.8033 and the sigma level became 3.2. The conclusion is that by reducing the defect rate and increasing the sigma value, the improvement solution can be used as a reference for future production in order to maintain the company's product quality.